Penafsiran Ayat-Ayat Tentang Golongan Orang-Orang Yang Dicintai Allah Dalam Tafsir Al-Azhar - M Ghifari Ramadhani; Muhammad Amrullah; Fajar Murdianto (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
This study analyzes the interpretation of Quranic verses about the group of people loved by Allah SWT based on the Tafsir al-Azhar by Buya Hamka. The method used is qualitative research with a library research approach. This study collects and analyzes verses related to the theme, referring to the book “al-Mu’jam al-Mufahras li Alfazh al-Qur`an al-Karim” by Muhammad Fuad Abdul Baqi, and then interprets these verses according to the Tafsir al-Azhar. The research also employs a thematic method to gain a deeper understanding of the secrets contained in the Quran regarding Mahabbatullah (love for Allah). The results show that the group of people loved by Allah are those who have faith and piety, follow the teachings of the Prophet Muhammad, and continually strive to maintain and enhance their faith and piety. Tafsir al-Azhar provides a deep and relevant explanation of contemporary issues, using a social and cultural approach that resonates with Malay-Minangkabau culture. This study is expected to serve as a guide for Muslims in understanding and practicing Islamic teachings to attain love and forgiveness from Allah Ta’ala. Keywords: Tafsir al-Azhar, Buya Hamka, People who loved by Allah.